OSTEOPOROSIS HEALTH BELIEF, KNOWLEDGE LEVEL AND RISK FACTORS IN INDIVIDUALS WHOSE BONE MINERAL DENSITY WAS REQUIRED - Gulpinar Aslan; Dilek Kilic (Belitung Raya Foundation, Indonesia, 2017)
Aim: This descriptive-relational study aims to identify osteoporosis health belief, knowledge level and risk factors in individuals whose bone mineral density was required. Method: Target population of the study was 110 men and 126 women aged 35 and over, who applied to Atatürk University Aziziye - Yakutiye Research Hospital Nuclear Medicine Center Bone Densitometer Unit between January 2010 and October 2010. No sampling was performed, the whole target population was involved in the study. Data were collected through the Personal Information Form that included socio-demographic features, the osteoporosis health belief scale, the osteoporosis self-efficacy scale and the osteoporosis knowledge test. Results: The osteoporosis health belief score of the participants was 139.99±14.79, osteoporosis knowledge score was 10.06±4.30, and osteoporosis self-efficacy score was 742.00±213.44. Among osteoporosis health beliefs, women’s susceptibility, seriousness, barriers of exercise, and barriers of calcium mean scores were found to be higher than those of men (p<0.001). Men’s osteoporosis self-efficacy scale and sub-dimensions mean scores were found to be higher in comparison to women (p<0.001). DEXA analysis results show that 57.1% of the women and 27.3% of the men were diagnosed with osteoporosis. Conclusion: According to the Logistic regression analysis that aimed to identify the risk factors having roles in Osteoporosis diagnosis, the affecting risk factors were gender, age, and medicine use. As for women, logistic regression analysis showed that the risk factors were education level – being illiterate, medicine use, osteoporosis story in family, and 4 or more deliveries.